Fast Facts: Cardiac Arrhythmias - Kaye, Gerry; Lemery, Robert (S. Karger, 2018)
Our understanding of the mechanisms and management of cardiac arrhythmias has improved dramatically in recent years thanks to continuing basic research coupled with technological advances. 'Fast Facts: Cardiac Arrhythmias' translates this improved understanding into straightforward guidance for managing patients presenting with signs of cardiac arrhythmia.The third edition of this highly readable handbook has been thoroughly updated to include recent pharmacological advances, such as the gradual replacement of warfarin anticoagulation with the novel direct oral anticoagulants. Also discussed are technological advances, including the use of smartphone and smartwatch systems to record heart rhythms, and the latest thinking on catheter and surgical ablation.New chapters have been added on the management of syncope and sudden cardiac death. These complement well-illustrated chapters describing normal conduction within the heart, the underlying mechanisms of arrhythmias and general investigation and management principles, as well as chapters discussing the definition, causes, diagnosis and management of specific arrhythmias.Other highlights include chapters on the rare, but increasingly recognized, inherited arrhythmias, as well as on the use of pacemakers and implantable cardioverter defibrillators.Of interest to primary care practitioners, nurses, medical students, technicians and cardiologists in training, this practical review of the mechanisms of heart rhythm abnormality and the contemporary therapies available provides a useful resource for improving patient care.Contents:• Normal conduction and mechanisms of arrhythmias• Presentation• Syncope• Sudden cardiac death• Investigation• Management principles• Supraventricular arrhythmias• Atrial flutter and atypical atrial flutter• Atrial fibrillation• Ventricular arrhythmias• Rare and inherited arrhythmias• Cardiac devices: pacemakers and defibrillators
Keywords: kardiovaskulární systém; kardiologie; srdeční arytmie; Cardiovascular System; Arrhythmias, Cardiac